PENGARUH PERENCANAAN PAJAK DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI: MANAJEMEN LABA - Khairisma Fadhilah Pramudhita; Adi Supriadi (JEKOS (Jurnal Ekonomi Dan Sosial), 2025)
This research aims to determine the effect of tax planning and deferred tax burden on earnings management with audit quality as a moderating variable in Consumer Non-Cylicals Sector Companies listed on the Indonesia Stock Exchange. The research period is the 2019-2023 period. The type of research used in this study is quantitative with secondary data. The determination of the sample of this study uses the purposive sampling method and based on the existing criteria, 25 company data were obtained and analyzed using panel data regression techniques with a fixed effect model to test the hypothesis. Hypothesis testing in this study uses panel data regression using Eviews version 10. The results of this study indicate that tax planning and deferred tax burden simultaneously show that they have a joint effect on earnings management. The results of this study indicate that partially tax planning has a positive effect on earnings management, while deferred tax burden does not affect earnings management, and audit quality is unable to moderate the relationship between tax planning and earnings management and audit quality is unable to moderate the relationship between deferred tax burden and earnings management.   Keywords: Tax Planning, Deferred Tax Expense, Earnings Management and Audit Quality